2011
DOI: 10.1177/030089161109700306
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between antioxidant status and cervical cancer: A case control study

Abstract: Levels of antioxidants significantly differed between the patients with cervical cancer and the controls, and no change in antioxidant levels was observed after treatment. Moreover, further studies evaluating the predictive value of glutathione levels on treatment response are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
14
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 23 publications
9
14
0
3
Order By: Relevance
“…Similar results were found by Senem et al who found that antioxidant status is altered in patients with cervical cancer compared to healthy controls 13 (Senem Demirici, et al, 2011). According to Chung et al, the cervical intraepithelial neoplasia was also associated with lower blood antioxidant capacity levels 14 (Chung HW, et al, 2004).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar results were found by Senem et al who found that antioxidant status is altered in patients with cervical cancer compared to healthy controls 13 (Senem Demirici, et al, 2011). According to Chung et al, the cervical intraepithelial neoplasia was also associated with lower blood antioxidant capacity levels 14 (Chung HW, et al, 2004).…”
Section: Discussionsupporting
confidence: 84%
“…Same results of elevated MDA levels were found in patients with cervical cancer compared to a control group by Senem Demirici et al, who stated oxidative damage leads to the formation of products like MDA and DNA damage may lead to mutagenesis, carcinogenesis and cell death 13 (Senem Demirici et al, 2011).…”
Section: Discussionmentioning
confidence: 75%
“…37 In another survey by Demirci et al on antioxidant status in 35 cervical cancer patients, the authors did not find significant differences between the levels of SOD, MDA and GPx status pre-RT and post-RT. 38 According to our knowledge, the reports regarding to the impact of age on the oxidant/antioxidant variables are limited. As previously mentioned in two age groups of patients, RT led to a significant decrease in some variables (GPx, SOD and TAS) and a non-significant increase in MDA and CAT levels.…”
Section: Discussionmentioning
confidence: 99%
“…Demirici et al [16] examined GSH, GSH-Px and SOD concentrations and the malondialdehyde (MDA) level before and after (chemo)radiotherapy in 35 patients, and compared the results to data from a control group of 35 healthy women. Antioxidant levels differed significantly between patients and healthy women.…”
Section: Discussionmentioning
confidence: 99%